Effectiveness of Wastewater Treatment Plant in Reducing PO₄ and NH₃-N Pollutants at Tk. III Brawijaya Hospital Surabaya - Udianto, Fauzi; Koesmantoro, Hery; Poerwati, Sri; Sunaryo (Jurnal Higiene Sanitasi, 2025)
Hospital wastewater contains hazardous pollutants that, if untreated, can harm the environment and human health. This study aimed to evaluate the efficiency of the Wastewater Treatment Plant (WWTP) at Tk. III Brawijaya Hospital Surabaya by analyzing the removal percentage of phosphate (PO₄) and ammonia nitrogen (NH₃-N) parameters. This descriptive research collected wastewater samples from the inlet, primary, secondary, tertiary, and outlet stages of the WWTP. Laboratory analysis was conducted from September to December 2023 to measure PO₄ and NH₃-N concentrations. Results showed that the average removal percentage for phosphate was 70%, while ammonia nitrogen showed a removal rate of 33%. The concentration of PO₄ decreased from 0.01 mg/L at the inlet to 0.003 mg/L at the outlet, while NH₃-N concentrations dropped from 0.9 mg/L to 0.6 mg/L. Although the phosphate concentration met the regulatory standard, the ammonia nitrogen concentration remained above the threshold set by East Java Governor Regulation No. 72/2013 (0.1 mg/L). In conclusion, the WWTP demonstrated moderate efficiency in reducing phosphate but inadequate performance in removing ammonia nitrogen. Further improvements in aeration processes and increased retention times are recommended to enhance the treatment efficiency and ensure compliance with environmental regulations.